Feminist and Materialist Philosophies of History in Caryl Churchill’s Top Girls - Sophie Poole (Meliora, 2022)
The first act of Caryl Churchill’s Top Girls does away with temporal boundaries, inviting women across historical periods, artistic masterworks, and literary epics to a dinner party. During the evening, the women share their life stories, interrupt each other, and attempt to be heard over the roar of their fellow guests. In some ways, it resembles an indecipherable oral history. What is history if not indecipherable? It is the role of the historian to wade through primary and secondary sources, cultural memories and forgotten artifacts, in order to construct a written, visual, or auditory historical narrative. Thus, a history as we consume it, although based in fact, necessarily relies on narrative structure. Top Girls reminds us that history is like any other narrative: shaped by social, political, and economic forces; made unintelligible, fantastical, and surreal at times, by representative modes and their failings. By playing with the notion of history, notably combining fictional and historical figures in the first act, Top Girls emphasizes the claim that history is, among other things, reliant on both factual and fictional elements, like concrete dates and narrative structures. Top Girls narrows in on two models of historical narratives: the feminist history and materialist history. In this play, there are only women onstage. Women picture, or reference, the men in their past and present—an alcoholic father, a lousy ex-husband, an insecure coworker, Rocky Mountain Jim, and the Emperor of Japan—but a man never sets foot on stage. Only women enter and exit, only women go to and from work, only women tell their histories, signaling Churchill’s dual interest in a Marxist philosophy of history and the notion of a feminist history, which emerged in the feminist movement in the ‘70s and ‘80s. Through the dramatic form, which provides a fantastical element, Churchill animates and complicates history as a feminist and socialist practice.